2016
DOI: 10.1186/s12936-016-1587-9
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of Plasmodium falciparum gametocyte infections in school-age children using molecular detection: patterns and predictors of risk from a cross-sectional study in southern Malawi

Abstract: BackgroundIn endemic areas, many people experience asymptomatic Plasmodium infections, particularly older children and adults, but their transmission contribution is unknown. Though not the exclusive determinant of infectiousness, transmission from humans to mosquitoes requires blood meals containing gametocytes. Gametocytes often occur at submicroscopic densities, challenging measurement in human populations. More sensitive molecular techniques allow better characterization of gametocyte epidemiologic pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
96
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(111 citation statements)
references
References 54 publications
14
96
1
Order By: Relevance
“…This study revealed that P. falciparum mature gametocytes can also be sourced from used RDTs. In addition to quantifying the number of DNA amplification cycles, SYBR Green makes it possible to estimate the number of gametocyte copies [9,19,20]. The number of copies would have allowed providing more precision on the estimation of the gametocyte density in this study [20].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This study revealed that P. falciparum mature gametocytes can also be sourced from used RDTs. In addition to quantifying the number of DNA amplification cycles, SYBR Green makes it possible to estimate the number of gametocyte copies [9,19,20]. The number of copies would have allowed providing more precision on the estimation of the gametocyte density in this study [20].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of mature gametocytes (stage V) in the human peripheral blood is the determining factor in the maintenance and increase of malaria transmission [1]. In Senegal, progress in the fight against malaria led the program to become part of the regional elimination of malaria by introducing primaquine in the management of the disease in the north of the country in order to reduce malaria gametocyte carriage in the population and block the transmission of the disease [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations